Advances in Zebrafish as a Comprehensive Model of Mental Disorders - Wang, Lei; Liu, Fan; Fang, Yimeng; Ma, Jiahui; Wang, Jiawei; Qu, Linkai; Yang, Qinsi; Wu, Wei; Jin, Libo; Sun, Da (Depression and Anxiety, 2023)
As an important part in international disease, mental disorders seriously damage human health and social stability, which show the complex pathogenesis and increasing incidence year by year. In order to analyze the pathogenesis of mental disorders as soon as possible and to look for the targeted drug treatment for psychiatric diseases, a more reasonable animal model is imperious demands. Benefiting from its high homology with the human genome, its brain tissue is highly similar to that of humans, and it is easy to realize whole-body optical visualization and high-throughput screening; zebrafish stands out among many animal models of mental disorders. Here, valuable qualified zebrafish mental disorders models could be established through behavioral test and sociological analysis, which are simulated to humans, and combined with molecular analyses and other detection methods. This review focuses on the advances in the zebrafish model to simulate the human mental disorders; summarizes the various behavioral characterization means, the use of equipment, and operation principle; sums up the various mental disorder zebrafish model modeling methods; puts forward the current challenges and future development trend, which is to contribute the theoretical supports for the exploration of the mechanisms and treatment strategies of mental disorders.